A Vision of Internet of Things - Sabeena, S; Jaganathan, M (International Journal of Computer Sciences and Engineering, 2019)
The Internet of Things (IoT’s) fast growth is affected by resource use and fears regarding privacy and security. An answer put together addressing security, efficiency, privacy, and measurability is required to support continued growth. We have a tendency to propose an answer shapely on human use of context and data, leveraging cloud resources to facilitate IoT on affected devices. We have a tendency to applying method information to provide security through abstraction and privacy through remote data fusion. We have a tendency to define the components and contemplate the key ideas of the “data proxy” and the “cognitive layer.” The information proxy uses system models to digitally mirror objects with lowest input information, whereas the cognitive layer applies these models to monitor the system’s evolution and to simulate the impact of commands before execution. The data proxy permits a system’s sensors to be sampled to fulfill a such quality of information target with lowest resource use.